Early congenital syphilis still occurs. Issue 12 (December 1985) - Ewing, C I; Roberts, C; Davidson, D C; Arya, O P
Abstract : Seven cases of early congenital syphilis have been recorded in the past 10 years in the Mersey Regional Health Authority. Antenatal serology was initially negative in five mothers, who were either incubating or acquired the infection later, and treatment had probably failed in two women given erythromycin for syphilis during pregnancy. Serology should be repeated later in pregnancy in those at high risk. Social factors that define this group include women who book for antenatal care late in pregnancy, have a past history of sexually transmitted disease, and have multiple consorts. Clinical signs in the infant such as failure to thrive, hepatosplenomegaly, symmetrical rash, rhinitis, and osteochondritis should alert the clinician to the possibility of congenital syphilis. Adequate management of mother and baby requires close liaison between the genitourinary physician, microbiologist, obstetrician, and paediatrician. Penicillin remains the treatment of choice.